Land Conversion and Its Impact on Socio-economic Life of Society (A Case Study in Tolangohula Subdistrict, Gorontalo) - Rauf A. Hatu (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Changes that occur in the form of a shift of ownership rights over agricultural land for the benefit of sugar cane plant life causes changes in farmers’ polls include shifting patterns of livelihoods, loss of agricultural land as a source of life of farmers to patterns of social life of farmers such as decrease in farmers’ income, changes of kinship and familial aspects, changes in family roles, changes in the status of farmers as well as changes in work and business opportunities in the life of farmers.Keywords: Functional Shift, Social Economic, Society